2003
DOI: 10.1007/s00436-003-0946-y
|View full text |Cite
|
Sign up to set email alerts
|

The rabbit coccidium Eimeria flavescens Marotel and Guilhon, 1941: an electron microscopic study of its life cycle

Abstract: The endogenous cycle of Eimeria flavescens was studied in specific pathogen-free rabbits by means of histology and transmission electron microscopy. In total, five asexual generations were observed and two types of meronts and merozoites were found in each generation. Type A gave rise to a smaller number of thick polynucleate merozoites in which daughter merozoites were formed by endomerogony, while in the type B meronts slender uninucleate merozoites arose from ectomerogony. The first generation meronts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
(26 reference statements)
0
15
0
2
Order By: Relevance
“…The studies on their life cycles (Norton et al 1979, Licois et al 1992, Pakandl et al 2003 showed that the last generation of meronts is developed at 7 DPI. At 14 DPI, only gamonts and oocysts are present in the intestine and the rabbits excrete oocysts, but their numbers are lower than at 10-12 DPI.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on their life cycles (Norton et al 1979, Licois et al 1992, Pakandl et al 2003 showed that the last generation of meronts is developed at 7 DPI. At 14 DPI, only gamonts and oocysts are present in the intestine and the rabbits excrete oocysts, but their numbers are lower than at 10-12 DPI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the type B meronts produced 30-150 merozoites in the original strain (Pakandl et al 2003), but only 20-60 in the PL. Surprisingly, not the last asexual generation, like in other rabbit coccidia (Pakandl et al 1996a(Pakandl et al , 1996c, but two preceding generations were lacking in the life cycle of PL.…”
Section: Discussionmentioning
confidence: 98%
“…A pure strain of E. flavescens (strain Va´cha) was previously used to study endogenous development of this species (Pakandl et al 2003).…”
Section: Parasite Strainmentioning
confidence: 99%
See 2 more Smart Citations